A new species of Brassica (Brassicaceae) from Bolkar Mountains (Türkiye) with morphological and molecular evidence - Başköse, İsa; Özüdoğru, Bariş; Savran, Ahmet; Keski̇n, Ali̇ (Phytotaxa, 2023)
Brassica huseyin-duralii from Niğde province in the Central Anatolian region of Türkiye is described and illustrated here as a new species of the tribe Brassiceae. It resembles B. repanda but differs from that species by its combination of woody caudex, leaf structure, and rosette and stem leaf shapes. It is also similar to B. elongata, from which it differs by its stem length, basal and stem leaf shapes and hair types, number of flowers, siliqua position and its width. This classification is also supported by phylogenetic analyses of nuclear ribosomal ITS data with B. huseyin-duralii and B. elongata constituting a monophyletic clade. The diagnosis, description, distribution and habitat of a new species, its distribution map and diagnostic key to Turkish Brassica species, are given; a Turkish name and IUCN Red List category are suggested.